Speech at the Session on New Challenges and Solutions for the World’s Sustainable Development - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group (WBG), spoke about how the global economy as a whole is in a period of strengthening growth, and this momentum in growth is driven by global manufacturing activity and trade, broadly stable financing conditions, and stabilized commodity prices. Escalating trade protectionism in major economies threatens to derail the rebound in global trade. He explained the severe consequences, especially for emerging markets and developing economies (EMDEs) that rely on trade for growth and development. He insisted on the need to maximize financing for development by leveraging the private sector and optimizing the use of scarce public resources. He spoke about the development of the joint principles for crowding in private sector finance. Crowding in private finance should free up public funds to invest more in people. He concluded by saying that WBG can make the global market system work for everyone through sustainable development, including inclusive economic growth, investing in people, and building resilience to shocks and threats.